2019
DOI: 10.1002/jpln.201800376
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cattle slurry application techniques on N2O and NH3 emissions from a loamy soil

Abstract: We determined N2O fluxes from an unfertilized control (CON), from a treatment with mineral N‐fertilizer (MIN), from cattle slurry with banded surface application and subsequent incorporation (INC), and from slurry injection (INJ) to silage maize (Zea mays, L.) on a Haplic Luvisol in southwest Germany. In both years, amount of available N (total N fertilized + Nmin content before N application) was 210 kg N ha−1. In the slurry treatment of the 1st year, 140 kg N ha−1 were either injected or incorporated, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 68 publications
3
14
0
Order By: Relevance
“…The high temporal variability of N 2 O fluxes in this study, with increased flux rates after application of crop residues or organic fertilizers and after rainfall events, was similarly documented in other experiments (Pfab et al, 2012;Herr et al, 2019). Ultimately, N 2 O fluxes leveled off 30 days after digestate application in both years with drying of the soil during warm periods with low rainfall.…”
Section: Temporal N 2 O and 15 N-n 2 O Fluxessupporting
confidence: 84%
See 2 more Smart Citations
“…The high temporal variability of N 2 O fluxes in this study, with increased flux rates after application of crop residues or organic fertilizers and after rainfall events, was similarly documented in other experiments (Pfab et al, 2012;Herr et al, 2019). Ultimately, N 2 O fluxes leveled off 30 days after digestate application in both years with drying of the soil during warm periods with low rainfall.…”
Section: Temporal N 2 O and 15 N-n 2 O Fluxessupporting
confidence: 84%
“…In a field study, NH + 4 -N-labeled cattle slurry was applied, which produced higher fertilizer-derived N 2 O emissions within the first 10 days, but higher soil-derived N 2 O 11-22 days after application (Dittert et al, 2001). However, the study was carried out on grassland and using the injection technique (Dittert et al, 2001), which has been reported to increase N 2 O emissions compared to trail hose application with immediate incorporation (Herr et al, 2019).…”
Section: Contribution Of Digestate N and Soil N Pool To N 2 O Emissionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the beneficial reduction of NH 3 losses, slurry INJ can promote anaerobic conditions in the injection slot and thus stimulates N 2 O release from denitrification [17,18]. The high N 2 O emission after cattle slurry INJ can even exceed the NH 3 loss following slurry INC with a disc harrow two hours after broadcast application [19].…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, many studies have been carried out in order to find innovative solutions able to mitigate the impact of livestock farming on GHG emissions, including covering slurry tanks, manure composting, acidification, anaerobic digestion, solid-liquid separation, dilution, and slurry aeration [1,2]. Other practices concern waste disposal on the field such as the addition of chemical additives [3] and the injection of slurry into the soil [4]. Aeration is an alternative practice to treat slurry.…”
Section: Introductionmentioning
confidence: 99%